Radiation Dosimetry Of Patients Undergoing 18f-Fdg Pet-Ct: A Retrospective Study - Hussin, Dhalisa (2018)
18F-FDG PET-CT patients are exposed to radiation doses from radiopharmaceuticals and the CT component respectively. The objective of this study was to perform the patient dose assessment based on calculations and measurements. The collected data were of 234 adults who underwent single PET-CT exams while 83 were those who underwent another sequential PET-CT examination on the same day of appointment at Institut Kanser Negara (IKN). 25 paediatrics underwent a single PET-CT examination. Organ dose assessment was performed using the PMOD and OLINDA/EXM software for heart, liver, kidney and urinary bladder. For adults the mean residence time result for liver is the longest, followed by kidney, urinary bladder and heart with mean average of 0.593 h ± 0.055 h, 0.434 h ± 0.031h, 0.361 h ± 0.061h and 0.326 h ± 0.024 h respectively. The mean result for organ absorbed dose of adult was 0.028 mGy, 0.045 mGy, 0.084 mGy and 0.006 mGy for heart, kidney, liver and bladder respectively. The whole-body PET-CT effective dose was determined from ICRP guidelines and the result of single and sequential PET-CT examination for adult was 16.69 mSv ± 4.01 mSv and 23.25 mSv ± 2.67 mSv respectively, while, paediatric patient ranged from 8.24 mSv ± 2.01 mSv to 14.23 mSv ± 2.67 mSv within the age from 0 to 16 years old. The patient mean dose rate reading at the surface and at 1 m before being discharged was 106.09 μSvhr-1 ± 40.33 μSvhr-1 and 7.55 μSvhr-1 ± 1.05 μSvhr-1 respectively. The estimation of mean urine excretion was 31.47 MBq ± 19.89 MBq within 185.25 min ± 30.32 min of spent time in this Centre. The result of this study for organ absorbed and whole-body PET-CT effective dose is relevant as the selection of patient was suspected with metastasis disease and the patient discharged level from this Centre is safe for public.